Study of Abiotic and Biotic Parameters Affecting the Abundance of Mosquito Larvae (Diptera: Culicidae) in the Region of Fez (Morocco) - Mouatassem, Touria Filali; El Ouali Lalami, Abdelhakim; Faraj, Chafika; Rais, Noureddine; Guemmouh, Raja (International Journal of Zoology, 2020)
Mosquitoes cause significant human health issues. However, very few studies have attempted to examine the question of how abiotic and biotic factors affect the abundance of Culicidae in the larval habitat. The objective of this study was to analyze the influence of biotic and abiotic factors on the increase of the most common mosquito species in the Fez region (Central Morocco). Larvae mosquitoes were sampled by standard dipping technique in four different types of macrohabitats, between November 2015 and November 2016. Each mosquito specimen was morphologically identified by the Moroccan Culicidae key and the Brunhes key. The analysis was done using R analysis software. We collected a total of 772 mosquito larvae belonging to nine different species, five of which are considered of medical interest. Culex pipiens (Linnaeus, 1758), known as the major vector in the transmission of West Nile virus fever (WNV), was the most common species of all mosquito larvae collected. The results of Poisson regression analysis showed that factors such as the presence of green filamentous algae, vegetation cover, and debris were found to be positively significant in the distribution of the genus Culex. However, there was insufficient evidence to determine the parameters that are capable of estimating the abundance of Anopheles. The findings have also estimated that biotic and abiotic factors can lead to significant variation in the abundance of Culex perexiguus (Theobald, 1903), Culex theileri (Theobald, 1903), and Culex pipiens (Linnaeus, 1758). Identifying the priority parameters governing the proliferation of mosquitoes in the region of Fez can be one of the key elements for better vector control.